Antibodies‐to‐infliximab accelerate clearance while dose intensification reverses immunogenicity and recaptures clinical response in paediatric Crohn's disease. Issue 5 (22nd December 2021) - Colman, Ruben J.; Xiong, Ye; Mizuno, Tomoyuki; Hyams, Jeffrey S.; Noe, Joshua D.; Boyle, Brendan; D'Haens, Geert R.; van Limbergen, Johan; Chun, Kelly; Yang, Jane; Rosen, Michael J.; Denson, Lee A.; et al.
Summary: Background: Antibodies to infliximab (ATI) are associated with secondary loss of response and increased risk for drug reactions. Limited studies have associated ATI with increased infliximab clearance. Aims: We assessed the impact of ATI on infliximab clearance and loss of response in an inception paediatric Crohn's disease cohort with 1‐year follow‐up. Methods: This multi‐centre prospective cohort study collected peak and trough serum infliximab/ATI concentrations from 660 infusions (78 patients) during the first year of therapy. Clinicians were blinded to these research labs. The primary outcome was the difference in infliximab clearance between ATI‐positive (ATI) and ATI‐negative (no‐ATI) patients. Secondary outcomes included pre‐treatment predictors of ATI (including HLA‐DQA1 genotyping). Clinical remission, loss of response and infliximab clearance were compared between pre‐ATI, during ATI and following ATI resolution with MANOVA. Time to ATI was calculated by Cox proportional Hazards model. Results: ATI were detected in 68% (53/78) patients with a median concentration of 76 ng/mL (range 23‐1828). Maximum ATI concentration was <200 ng/mL in 73.6% (39/53). Median clearance in ATI patients was higher (with higher clearance if loss of response), compared to no‐ATI patients ( P < 0.001). Neutrophil CD64 ratio >6 and starting dose <7.5 mg/kg independently predicted ATI in multivariable regression, while HLA‐DQA1*05 presence did not. Dose adjustment resolved ATI in 37.5% (12/32) patients with concomitant infliximab concentration and clearance recovery. A maximum ATI level of ≤99 ng/mL predicted ATI resolution (area under the receiver operating curve 0.80 [95% CI 0.64‐0.96]). Conclusions: In this real‐world cohort, ATI as low as 23 ng/mL impacted drug clearance. Our data suggest that dose optimisation for low‐level ATI can improve infliximab clearance and prevent loss of response. Abstract : Antibodies to infliximab are common and result in rapid drug clearance in pediatric Crohn's disease.